Altered Balance of Pro-Inflammatory Immune Cells to T Regulatory Cells Differentiates Symptomatic From Asymptomatic Individuals With Anti-Nuclear Antibodies - Gupta, Rashi; Vanlieshout, Emma; Manion, Kieran; Bonilla, Dennisse; Kim, Michael; Muñoz-Grajales, Carolina; Nassar, Carol; Johnson, Sindhu R.; Hiraki, Linda T.; Ahmad, Zareen; Touma, Zahi; Bookman, Arthur; et al. (Frontiers in Immunology, 2022)
Systemic Autoimmune Rheumatic Diseases (SARDs) are characterized by the production of anti-nuclear antibodies (ANAs). ANAs are also seen in healthy individuals and can be detected years before disease onset in SARD. Both the immunological changes that promote development of clinical symptoms in SARD and those that prevent autoimmunity in asymptomatic ANA+ individuals (ANA+ NS) remain largely unexplored. To address this question, we used flow cytometry to examine peripheral blood immune populations in ANA+ individuals, with and without SARD, including 20 individuals who subsequently demonstrated symptom progression. Several immune populations were expanded in ANA+ individuals with and without SARD, as compared with ANA- healthy controls, particularly follicular and peripheral T helper, and antibody-producing B cell subsets. In ANA+ NS individuals, there were significant increases in T regulatory subsets and TGF-ß1 that normalized in SARD patients, whereas in SARD patients there were increases in Th2 and Th17 helper cell levels as compared with ANA+ NS individuals, resulting in a shift in the balance between inflammatory and regulatory T cell subsets. Patients with SARD also had increases in the proportion of pro-inflammatory innate immune cell populations, such as CD14+ myeloid dendritic cells, and intermediate and non-classical monocytes, as compared to ANA+ NS individuals. When comparing ANA+ individuals without SARD who progressed clinically over the subsequent 2 years with those who did not, we found that progressors had significantly increased T and B cell activation, as well as increased levels of LAG3+ T regulatory cells and TGF-ß1. Collectively, our findings suggest that active immunoregulation prevents clinical autoimmunity in ANA+ NS and that this becomes impaired in patients who progress to SARD, resulting in an imbalance favoring inflammation.